(untitled) (Journal of Applied Oral Science, 2012)
As is commonly understood, the root canal morphology of the maxillary molars is usually complex and variable. It is sometimes difficult to detect the distobuccal root canal orifice of a maxillary second molar with root canal treatment. No literature related to the distobuccal root canals of the maxillary second molars has been published. Objective: To investigate the position of the distobuccal root canal orifice of the maxillary second molars in a Chinese population using cone-beam computed tomography (CBCT). Material and methods: In total, 816 maxillary second molars from 408 patients were selected from a Chinese population and scanned using CBCT. The following information was recorded: (1) the number of root canals per tooth, (2) the distance between the mesiobuccal and distobuccal root canal orifice (DM), (3) the distance between the palatal and distobuccal root canal orifice (DP), (4) the angle formed by the mesiobuccal, distobuccal and palatal root canal orifices (∠PDM). DM, DP and ∠PDM of the teeth with three or four root canals were analyzed and evaluated. Results: In total, 763 (93.51%) of 816 maxillary second molars had three or four root canals. The distance between the mesiobuccal and distobuccal orifice was 0.7 to 4.8 mm. 621 (81.39%) of 763 teeth were distributed within 1.5-3.0 mm. The distance between the palatal and distobuccal orifice ranged from 0.8 mm to 6.7 mm; 585 (76.67%) and were distributed within 3.0-5.0 mm. The angle (∠PDM) ranged from 69. 4º to 174.7º in 708 samples (92.80%), the angle ranged from 90º to 140º. Conclusions: The position of the distobuccal root canal orifice of the maxillary second molars with 3 or 4 root canals in a Chinese population was complex and variable. Clinicians should have a thorough knowledge of the anatomy of the maxillary second molars.